Implementation of Ice Breaking on PJOK Learning Motivation - Savitri, Vira Nur; Santosa, Agus; Kurnia, Dedi (STKIP Paasundan Press, 2023)
This study aims to determine the implementation of ice breaking on student learning motivation. The research method used is Experiment. The population of grade 5 SDN 1 Wanayasa was 32 students, sampling was carried out using the Total Sampling technique, the research sample amounted to 32 students. The research instrument used a questionnaire (questionnaire). Hypothesis testing using paired Sample T test, which is to test the normality and homogeneity of the research data Because the significance value is less than 0.0020 <0.05, it can be concluded that the research data is accepted. The results of the increase from the Pre-test and Post-test increased by 5.7%. So it can be concluded that ice breaking can increase student learning motivation. So that it can spur students to be more active in the learning process at school.